Pengaruh Motivasi dan Disiplin terhadap Prestasi Belajar Mahasiswa Jurusan Manajemen Universitas Sumatera Barat - Sudirman (SAFE-Network, 2023)
This Research Aims to Know The Influence of Motivation and Discipline On Student Achievement Management Department, University of West Sumatra. Taking this title is based on the lack of learning motivation of students majoring in management compared to students in other majors so that discipline is not well implemented and student learning achievement when compared to students in other majors such as accounting, health etc. This study uses a type of quantitative research. The data taken is in the form of primary data by distributing questionnaires to students majoring in management at the University of West Sumatra. This study conducted research instrument tests, classical assumption tests, hypothesis testing using SPSS version 21. With the results of the research stating that seeing the results of the tests that have been carried out proves that partially or simultaneously both variables have a significant effect, and it can also be seen that Adjusted R Square is 0.522 or of 52.2% This means that 52.2% of learning achievement variables are influenced by motivation and discipline, the remaining 47.8% are influenced by other variables outside of this research variable.